A serendipitous one-step conversion of 3H-1,2-dithiole-3-thione to (E)-3-(1-(alkylthio)alkylidene)-3H-1,2-dithiole: an experimental and theoretical study - Couto, Marcos (2014)
In the course of our studies on 3H-1,2-dithiole-3-thione synthesis, a serendipitous reactivity with α-haloketones, in the presence of excess of potassium iodide, has been observed. Instead of the expected reaction of the nucleophile in a remote point of the molecule, we have obtained a product resulted from the electrophile character of the thiocarbonyl moiety on the 3-position of the 1,2-dithiole. In order to obtain an efficient protocol in terms of energy efficiency, this methodology was studied under conventional and microwave heating with similar or better results in the latter conditions. Simplicity and great efficiency in this one-step transformation are some of the advantages of this reaction. Moreover, the results can be explained according to the Pearson's hard and soft acid base theory.